Nanoscale Structure and Relaxation in Zr50Cu45Al5 Bulk Metallic Glass - Voyles, P. M.; Stone, D. S.; Kramer, M. J.; Kalay, I.; Kalay, Y. E.; Melgarejo, Z. H.; Hwang, Jinwoo (My University, 2012)
Hybrid reverse Monte Carlo simulations of the structure of Zr50Cu45Al5 bulk metallic glass incorporating medium-range structure from fluctuation electron microscopy data and short-range structure from an embedded atom potential produce structures with significant fractions of icosahedral- and crystal-like atomic clusters. Similar clusters group together into nanometer-scale regions, and relaxation transforms crystal-like clusters into icosahedral clusters. A model refined against only the potential does not agree with the fluctuation microscopy data and contains few crystal-like clusters.
http://dx.doi.org/10.1103/PhysRevLett.108.195505
Keywords: medium range order; metallic glass; fluctuation electron microscopy